Phenomenology of a symbolic dish. What porceddu teaches us about food, meaning and Identity - Sedda, Franciscu (E|C, 2020)
The analysis of Sardinian dish su porceddu allows us to focus on four relations typical of a semi-politics of nutrition. The relation between continuity or discontinuity of the values ​​associated with an animal, a food, a dish. The relation between oneself and others: that is, the way in which the polemical dimension of culture connects certain dishes to certain places. The link between knowledge and taste: that is, how a scientific discourse can produce or reveal a dynamic of political valorisation that brings together naturalistic, economic, political, gustatory "data" to produce a peculiar form of cultural systematization and self-description. Finally, the link between memory and forgetfulness.